KEJAHATAN GENOSIDA TERHADAP ETNIS ROHINGNYA DALAM PERSPEKTIF HUMANITER DAN PERTANGGUNGJAWABAN BERDASARKAN STATUTA ROMA (ICC) - Effendi, Erdianto; Edorita, Widia; ', WAHYUNI (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Inter-ethnic problems in Myanmar long time ago, since Myanmar's independence in 2012 until the spawning of heart-wrenching news. These problems with their deeds and cruelty received by Ethnic Rohingya Muslims, to their ethnic cleansing or genocide. The conflict in Myanmar is motivated by several things, namely: First Rohingya is this distinction is clear from the use of language, color, and religion. Both cases of violence in the Muslim Rohingya began in June 2012, which is deadly on the western Arakan State between ethnic Buddhists and Muslim Rohingya. Third konfilik procession by Muslim Rohingya communities began with the increase in human rights violations and violence. Fourth citizenship that is not owned Rohingya as well as accountability for crimes under the ICC applies to individuals and commanders on orders from superiors. The purpose of this thesis is; First, the view of humanitarian law related to the Genocide crimes and human rights violations against ethnic Rohingya set out in the Rome Statute (ICC). Second, accountability for the ethnic Rohingya in view of the Rome Statute (ICC). Research conducted by the researchers used a normative juridical approach, the research discusses the principles of law. If viewed from its nature, this research belong to the descriptive, meaning this study illustrates the fact that studied by researchers. From the research problems consists of two things can be concluded: First, gross human rights violations contained in the Universal Declaration of Human Rights regarding the rights that exist in humans, as well as some of the International Convention on Human Rights were also set up. International crimes in the ICC crimes include genocide and crimes against Rohingya Humanity under Article 6 and Article 7 of the Rome Statute. Second, accountability Genocide against the perpetrators carried out by individuals, command of superior orders and official positions of government by virtue of Article 25: Individuals responsible and can be punished for his actions, Article 27: All persons without distinction of official position, either as a Head of State or Government , parliamentarians, government officials can be held accountable, and Article 28: military command is criminally responsible for crimes by troops under his control / authority to know the troops had committed or was about to commit such crimes, or the failure to prevent, Tops it knows, or consciously disregarded information to indicate that; Crimes related to activities that are within the responsibility by the Rome Statute.Keywords: Genocide - Rohingya - Violation of human rights - Accountability - the Rome Statute (ICC)